Employees Attitude Towards Performance Appraisal— A Case Study on Life Insurance Corporation (LIC) - Vadehra, Pallvi (Journal of Commerce and Trade, 2011)
The purpose of this research paper was to analyze the overall attitude of employees working in LIC (Life Insurance Corporation) India towards the performance appraisal system used by the organization. The study involves using some key questions to gauge satisfaction of Class I, Class II and Class III employees towards existing appraisal process and also to determine the relevance of this process in making decisions regarding job confirmation, transfer and promotion of LIC employees. In this paper we have determined how much satisfied are employees with the current method for appraising the performance and what are the limitations of using the existing method for performance evaluation. Results showed that though employees fairly consider appraisal as a vital tool towards their development, but there is significant difference in their views about effectiveness of current performance appraisal process in LIC. Interview results showed that only less than a quarter of respondents are of the view that the present performance system is effective and serves its purpose and majority of 80 per cent of the respondents feel that the system is just meeting the paper requirement and needs to be changed. Research data also shows that more than 70 per cent of employees are of the view that adequate training is must for appraisers to make the performance appraisal process work effectively.